2019
DOI: 10.3390/su11195322
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Business Model Innovation Employed by Small and Micro Travel Agencies in the Internet+ Era

Abstract: This study mainly investigated the factors affecting the business model innovation of small and micro travel agencies (SMTAs) in the Internet+ era. Based on a literature review, six hypotheses were proposed. To identify the influencing factors, the questionnaire, which was developed from previous studies, was distributed and 130 valid questionnaires were identified. Linear regression was used to test the hypotheses and further verify the relationship between each factor and the four dimensions of business mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Another study conducted on travel agencies in Tehran showed that service innovation is achieved through direct channels and indirectly affects performance (Lin-Lin et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted on travel agencies in Tehran showed that service innovation is achieved through direct channels and indirectly affects performance (Lin-Lin et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, starting from the definition of sustainable entrepreneurship, Tur-Porcar et al [129] consider that the most important stimulating factors are those related to behavior, followed by business factors, especially related to profit, entrepreneur, and human relations. In the same climate of opinion, Xue et al [130] show that the specific elements of the organizational context (internal and external) and the actions of stakeholders affect the sustainability of an organization. Moreover, more substantial support from the government, supply chain agents, and consumers could contribute to the successful implementation of sustainable business models [101].…”
Section: Substantiation Of Research Hypothesesmentioning
confidence: 99%
“…The current body of literature explores several factors that can affect BMI (Zhao et al, 2017;Foss and Saebi, 2017b;Xue et al, 2019). However, a review of the related literature shows that little attention has been paid to exploring the influence of managers' individual characteristics on BMI (Guo et al, 2013;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The current body of literature explores several factors that can affect BMI (Zhao et al. , 2017; Foss and Saebi, 2017b; Xue et al. , 2019).…”
Section: Introductionmentioning
confidence: 99%